Time‐resolved in situ tomography for the analysis of evolving metal‐foam granulates. (3rd August 2018) - García-Moreno, Francisco; Kamm, Paul H.; Neu, Tillmann R.; Banhart, John
Abstract : A setup for time‐resolved in situ tomography with up to 25 tomograms s −1 is implemented at the EDDI beamline, BESSY II, Germany. The capabilities of the methods are demonstrated by analysing the foaming behaviour of a metallic foam granulate. Abstract : An experimental setup has been developed that allows for capturing up to 25 tomograms s −1 using the white X‐ray beam at the experimental station EDDI of BESSY II, Berlin, Germany. The key points are the use of a newly developed, precise and fast rotation stage, a very efficient scintillator and a fast CMOS camera. As a first application, the foaming of aluminium alloy granules at 923 K was investigated in situ . Formation and growth of bubbles in the liquid material were observed and found to be influenced by the limited thermal conductivity in the bulk granules. Changes that took place between two tomographic frames separated in time by 39 ms could be detected and analysed quantitatively.